Quebec and Her Sisters in the Third Legal Family - Palmer, Vernon (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2009)
AbstractThe global legal landscape is populated with at least three legal families: civil, common, and mixed. This third family, and Quebec’s place within it, forms the subject of the 2008 Wainwright Lecture. Professor Vernon Palmer proposes that although jurisdictions in this family may share certain features, there is no single model of a mixed jurisdiction. A thriving legal system, like that in Quebec, inevitably draws support from its own distinctive social, cultural, and institutional context.The lecture proceeds by means of a five-fold exploration of the concept of “mixed jurisdictions”:An overview of the work of earlier legal scholars such as F.P. Walton, Robert Warden Lee, and T.B. Smith, tracing the origins of the concept back to its Egyptian roots, and then forward to its current academic reception;An examination of legal pluralism. Professor Palmer suggests that although pluralism provides a critical tool for recognizing and examining hybrid systems, its liberal and inclusive nature fails to produce a useful taxonomy of legal systems;A provisional definition of a classical mixed jurisdiction based on its typical shared features or components, highlighting the role that subjective awareness plays in identifying and shaping mixed jurisdictions;An explanation of the concept of a legal family and of the classification of mixed jurisdictions as a distinctive, third legal family;A discussion of the many ways in which two legal traditions may mix. Professor Palmer concludes the lecture by arguing that there is no single paradigm of a mixed jurisdiction. Quebec’s own unique experience helps illustrate this proposition.